Failure mechanism and fracture aperture characteristics of hard thick main roof based on voussoir beam structure in longwall coal mining. Issue 2 (22nd December 2019) - Zhang, Chunwang; Jin, Zhixin; Song, Xuanmin; Feng, Guorui; Li, Zhu; Gao, Rui; Zhu, Defu; Li, Chun
Abstract: The mechanism and fracture aperture of thick hard roof failure were theoretically analyzed from the perspective of elastoplastic mechanics. A uniform load cantilever beam was established by considering the voussoir beam structure and stress condition. According to the stress inverse principle in solving the plane strain problem, the internal stress component analytic solution was deduced. Considering the lateral thrust and shear force and by applying the Mohr‐Coulomb failure criterion, the plastic zone boundary equation was obtained. Further analysis of the equivalent stress, equivalent strain, elastic energy density, distortion energy density, and strain energy density was studied with blocks of four different lengths, combined with the rotation angles after failure, to analyze the fissure aperture between straight and curved fracture traces. The theoretical analysis reveals that the deviatoric effect plays the lead role in rupture initiation and propagation; the cracks will deflect during failure, and the fracture trace presents a curved shape. The variation of fracture aperture exhibits a tendency to increase first, then decrease, and then increase along the fracture trace. The analytical approach presented in this paper provides a theoretical basis for determining the main seepage channel flow in underground mining. Abstract : 1. Uniform load beam model was established considering the shear force and lateral thrust and stress components analytic solution was obtained based on elasticity inverse method 2. Plastic zone boundary equation was deduced with Mohr‐Coulomb failure criterion 3. Analyzed break mechanism from deviatoric stress component and strain energy density and contrast analysis the fissure aperture variation along fracture trace on four block.